Contradistinction of agency and stewardship theories: a brief discourse / Muslimah Mohd Jamil - Mohd Jamil, Muslimah (Faculty of Accountancy, 2021)
Accounting, corporate governance and auditing are among the areas that require perfect cooperation and mutual trust of humans in an organisation. Humans are required to play multiple roles and aligned them with one another. To synchronise this situation, many academicians and researchers will use two theories to explain how a person should behave. The theories are agency theory and stewardship theory. Therefore, this article will explore the discussion of these two theories by looking at their definition, orientation and limitation.